2020
DOI: 10.1055/s-0040-1713005
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Repair in Cats Using a Conical Coupling Mini 1.9 to 2.5 mm Locking Plate System

Abstract: Objective The aim of this study was to retrospectively evaluate the clinical application of the Fixin mini 1.9 to 2.5 system for the treatment of long bone fractures in cats. We proposed that the Fixin mini system would successfully stabilize long bone fractures in cats with a healing time and complication rate similar to those previously reported for feline fractures using other locking bone plate systems. Materials and Methods Medical records and radiographs of cats with long bone fractures stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…18 A third study using Fixin implant system in cats reported an 8.8 week mean time to radiographic union with 14% complication rate; 7% minor and 7% major complication rate. 19 Within that study, major complications consisted of implant deformation in ¾ cases with complications. Comparing our results to previously reported studies, fractures treated with the LLS had similar complication rates to other commercially available implants.…”
Section: Discussionmentioning
confidence: 99%
“…18 A third study using Fixin implant system in cats reported an 8.8 week mean time to radiographic union with 14% complication rate; 7% minor and 7% major complication rate. 19 Within that study, major complications consisted of implant deformation in ¾ cases with complications. Comparing our results to previously reported studies, fractures treated with the LLS had similar complication rates to other commercially available implants.…”
Section: Discussionmentioning
confidence: 99%